2022
DOI: 10.1080/15592324.2022.2129289
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous melatonin confers cold tolerance in rapeseed (Brassica napus L.) seedlings by improving antioxidants and genes expression

Abstract: Rapeseed ( Brassica napus L.) is an important oilseed crop globally. However, its growth and production are significantly influenced by cold stress. To reveal the protective role of exogenous melatonin (MEL) in cold tolerance, rapeseed seedlings were pretreated with different concentrations of MEL before cold stress. The results indicated that the survival rate was increased significantly by the MEL pretreatment under cold stress. Seedlings pretreated with 0.01 g L −1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…2019; Ritonga & Chen 2020; Lei et al . 2022). Nonetheless, plant response depends on various factors, including signal perception and transduction (Ganeshan et al .…”
Section: Effects and Responses Of Temperature Stress On Plants: An Ov...mentioning
confidence: 99%
See 1 more Smart Citation
“…2019; Ritonga & Chen 2020; Lei et al . 2022). Nonetheless, plant response depends on various factors, including signal perception and transduction (Ganeshan et al .…”
Section: Effects and Responses Of Temperature Stress On Plants: An Ov...mentioning
confidence: 99%
“…ROS substantially increase under CS, causing significant damage to proteins, lipids and cellular structures (Hassan et al 2021;Mittler et al 2022). Plants activate antioxidant defence systems to cope with the deleterious impacts of CS (Sun et al 2019;Ritonga & Chen 2020;Lei et al 2022). Nonetheless, plant response depends on various factors, including signal perception and transduction (Ganeshan et al 2008).…”
Section: Effects and Responses Of Temperature Stress On Plants: An Ov...mentioning
confidence: 99%
“…Antioxidant enzymes have been mainly reported to be the first line of defensive and protective mechanisms against any environmental factor such as abiotic stresses ( Lei et al., 2022 ; Mittler et al., 2022 ; Najafi-Kakavand et al., 2022 ; Rahman et al., 2022 ; Raza et al., 2022a ; Raza et al., 2022b ; Shahid et al., 2022 ; Shaukat et al., 2022 ; Bhardwaj et al., 2023 ). At first, the superoxide radicals are converted to H 2 O 2 by SOD activity which can be further decomposed into H 2 O by CAT and peroxidases ( Hasanuzzaman et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the increase in endogenous ABA content was closely related to the increase in chilling tolerance [18,19]. Exogenous application of ABA increased the chilling tolerance of different plant species, including Stylosanthes guianensis [10], Cucumis melo [20], and Zea mays [21]. ABA plays a major role in the stimulation of endogenous changes relating to cold acclimation [13,22].…”
Section: Introductionmentioning
confidence: 97%
“…Exposure to low temperatures induces oxidative stress through the accumulation of reactive oxygen species (ROS) [8,9]. Plants have evolved an efficient defense system against oxidative stress via enzymatic and non-enzymatic antioxidants [8][9][10]. Abscisic acid (ABA) is a key regulator of many aspects of plant growth and development in higher plants, such as the maturation of embryos, the dormancy of seeds, the development of flowers, and the growth of roots [11].…”
Section: Introductionmentioning
confidence: 99%